A Framework for Representing Ontology Mappings under Probabilities and Inconsistency - Calì, A; Lukasiewicz, T; Predoiu, L; Stuckenschmidt, H (CEUR−WS.org, 2008)
Creating mappings between ontologies is a common way of approaching the semantic heterogeneity problem on the Semantic Web. To fit into the landscape of semantic web languages, a suitable, logic-based representation formalism for mappings is needed. We argue that such a formalism has to be able to deal with uncertainty and inconsistencies in automatically created mappings. We analyze the requirements for such a mapping language and present a formalism that combines tightly integrated description logic programs with independent choice logic for representing probabilistic information. We define the language, show that it can be used to resolve inconsistencies and merge mappings from different matchers based on the level of confidence assigned to different rules. We also analyze the computational aspects of consistency checking and query processing in tightly integrated probabilistic description logic programs.